Characterisation of noise and sharpness of images from four digital breast tomosynthesis systems for simulation of images for virtual clinical trials. (24th February 2017) - Mackenzie, Alistair; Marshall, Nicholas W; Hadjipanteli, Andria; Dance, David R; Bosmans, Hilde; Young, Kenneth C
Abstract: In-depth evaluation of the noise and sharpness characteristics of FujiFilm Innovality, GE SenoClaire, Hologic Selenia Dimensions and Siemens Inspiration digital breast tomosynthesis (DBT) systems was performed with the intention of improving image simulation for virtual clinical trials. Noise power spectra (NPS) and modulation transfer function curves (MTF) were measured for planar modes and for the first and central projections for DBT modes. In DBT mode, the x-ray beam was blocked for the projections before the central projection in order to remove the influence of lag and ghosting from the previous images. A quadratic fit between the NPS and linearised pixel value gave the noise coefficients for planar and DBT imaging modes. The spatial frequencies corresponding to an MTF of 0.5 (MTF0.5 ) were calculated from the MTF measurements made on the breast support and at 40 mm above the breast support. This was done for the first and the central projections. The percentage of signal carried over from the first projection to subsequent images (lag) was measured using a slit. The noise associated with lag was also evaluated. The DBT modes typically had lower electronic noise coefficients but higher structural noise coefficients compared to the respective planar mode MTF0.5 measured 40 mm above the table was between 6% and 47% lower for continuous scanning systems compared to 1% lower for step and shoot systems. For wide angle DBT, the MTF0.5 of the first projection was 18% (FujiFilm) and 28% (Siemens) lower than for the central projection. Lag in the second projection was 2.2%, 0.3%, 0.8% for the FujiFilm, GE and Hologic systems respectively. In all cases, the noise associated with lag was negligible. Current modelling frameworks for virtual clinical trials of breast DBT systems need to be adapted to account for signals from lag and variations in the MTF at wide angles.